PERBAIKAN STABILITAS DINAMIS STSTEM 5OO KV JAWA-BALI MENGGUNAKAN UNIFIED POWBR FLOW CONTROLLER (UPFC) - Agus Junaidi; Adi Soeprijanto; Imam Robandi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
Recently, due to the progress of power electronics technology, a Flexible AC Transmission System (FACTS) has been used as an control device to improve the dynamic stability of a power sytem. One type of FACTS devices is Unified power Flow Conrroller (UPFC).This research investigate the great impact of UPFC to damp oscillation power system with injection model to the transmission line. The injection models is created in an equation active and reactive power supply of the UPFC.Pctckuge program is MATLAB used to excute lhe simulation the UPFC injection model to lhe damlt electromechanical oscillation. Examination was done by case study at an 500 KV Jawa-Bali electrical power system. Examination result show that UPFC installation can improve electric power system dynamic stabitify seen by the overshoot and settling time decrease.